"Stress entropic load" as a transgenerational epigenetic response trigger - Bienertová-Vašků, Julie; Nečesánek, Ivo; Novák, Jan; Vinklárek, Jan; Zlámal, Filip (Medical hypotheses, 2014)
Epigenetic changes are generally based on the switching of alternative functional or structural states and result in the adaptation of cellular expression patterns during proliferation, differentiation or plastic changes in the adult organism, whereas some epigenetic information can be passed on other generations while other is not. Hence, the principal question is: why is some information reset or resolved during the meiosis process and other is passed from one generation to another, or, in other words: what "adaptation trigger" level initiates transgenerationally transmitted epigenome change? Hereto, we propose a theory which states that stress, or, more specifically, the energy cost of an individual's adaptation to stress, represents a viable candidate for the transgenerational transmission trigger of a given acquired trait. It has been reported recently that the higher lifetime entropy generation of a unit's body mass, the higher the entropy stress level (which is a measure of energy released by a unit's organ mass) and the irreversibility within the organ, resulting in faster organ degradation and consequent health problems for the entire biological system. We therefore suggest a new term: "stress entropic load" will reflect the actual energetic cost of an individual's adaptation and may be used to estimate the probability of inducing transgenerational response once characterized or measured.
Keywords: fyziologický stres; Stress, Physiological; epigeneze genetická; lidé; entropie; Epigenesis, Genetic; Entropy; Humans